2017
DOI: 10.1017/s1742170517000540
|View full text |Cite
|
Sign up to set email alerts
|

School districts and their local food supply chains

Abstract: The 2015 Farm to School Census reports that during the 2013–2014 school year there were over 5200 farm to school (FTS) programs in the USA that involved 39,000 schools and 24.1 million children. These FTS programs are intended, in part, to increase market access and therefore the viability of farms and ranches. Accordingly, the majority of FTS programs involve local food procurement directly from farmers, from non-traditional suppliers that market locally branded food products such as ‘food hubs’, or from trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Governments could also support organizations that sell RGFFV, for example, through food procurement legislation of state-owned food outlets to prioritize inclusion of regional produce. This has been trialed in the USA in schools (e.g., Christensen et al [57]), military bases (e.g., Dunning et al [58]) and hospitals (e.g., Kendra et al [59]), although a number of barriers including negotiating with centralized procurement systems, maintaining food safety and seasonality of supply [58,60] have been identified. Implementing integrated ordering systems, sequencing market entry and growth, and facilitating flexible contracts that work for both the institution/s and the producer/s are recommended for increasing the proportion of RGFFV purchased by these institutions [60].…”
Section: Education Policy Practice and Research Recommendationsmentioning
confidence: 99%
“…Governments could also support organizations that sell RGFFV, for example, through food procurement legislation of state-owned food outlets to prioritize inclusion of regional produce. This has been trialed in the USA in schools (e.g., Christensen et al [57]), military bases (e.g., Dunning et al [58]) and hospitals (e.g., Kendra et al [59]), although a number of barriers including negotiating with centralized procurement systems, maintaining food safety and seasonality of supply [58,60] have been identified. Implementing integrated ordering systems, sequencing market entry and growth, and facilitating flexible contracts that work for both the institution/s and the producer/s are recommended for increasing the proportion of RGFFV purchased by these institutions [60].…”
Section: Education Policy Practice and Research Recommendationsmentioning
confidence: 99%
“…According to the 2013-2014 Farm to School Census, 65% of school districts buy local food through a distributor. Christensen, Jablonski, and O'Hara (2017) found that schools that purchase local products directly from farms and/or nontraditional distributors spend significantly less per student on non-milk local food purchases. The fact that intermediaries facilitate the majority of farm-to-school transactions also poses new challenges for identifying producers engaged in farmto-school sales and measuring supply and demand for local foods in schools.…”
Section: Farmer Survey Descriptive Statisticsmentioning
confidence: 97%
“…Buying local food products from distributors is the market channel that schools used most frequently, although making local food purchases directly from farmers and processors/manufacturers was also common (Christensen, Jablonski, and O'Hara 2017). Questions in the Farm to School Census did not solicit disaggregated information about which supply chains were used for specific food products.…”
Section: Local Seafood Purchases By Schoolsmentioning
confidence: 99%
“…The food budget of 93 New England colleges was $292 million. The use of food service management companies by schools is uncommon (Christensen, Jablonski, and O'Hara 2017). In contrast, 73% of New England colleges use food service management companies like Sodexo, while 27% have self-operated dining operations (FINE 2017a).…”
Section: Local Seafood Purchases By Collegesmentioning
confidence: 99%